Features of Surface Structures of Alumina and Titanium Dioxide Nanoparticles Produced Using Different Synthesis Methods. (23rd January 2018) - Syzrantsev, Vyacheslav; Paukshtis, Evgenii; Larina, Tatyana; Chesalov, Yuriy; Bardakhanov, Sergey; Nomoev, Andrey
Abstract : A comparative study of the scope and surface properties of alumina (Al2 O3 ) and titanium dioxide (TiO2 ) nanoparticles, synthesized using different methods, was carried out using Fourier-transform infrared spectroscopy (FTIR), ultraviolet UV-Vis diffuse reflection spectroscopy (UV-Vis DRS), and Raman spectroscopy, as well as X-ray diffraction methods. It is shown that the differences in the synthesis methods can change the surface properties of the nanoparticles, while maintaining the phase composition of the material. The nanoparticles of each material are shown to exhibit unexpected properties. In particular, the special luminescence characteristics of TiO2, a photon-energy shift from the rutile region into that region typical for the anatase, and a significant difference in the Lewis center concentration values for the alumina γ -phase were observed. This variation in the properties indicates the necessity to involve a wider range of analysis techniques and the importance of precisely characterizing the surface properties. To identify those nanoparticle functional properties that determine their interactions with other materials, a comprehensive study of their phase compositions and surface properties must be completed.